2012
DOI: 10.1177/0194599812445859
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cartilaginous Reinforcing Sutures on Initial Tracheal Anastomotic Strength

Abstract: Cartilaginous reinforcing sutures were found to provide a higher force requirement for tracheal anastomotic rupture when compared with anastomoses without these sutures. This improved stability in tracheal anastomosis may result in a decreased risk of early tracheal rupture after anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…9) This value range is between 51 and 179.9 Newtons in various human cadaver studies. 4,5,15) Bicer et al, in sheep, they found the rupture tension as 171.9 Newtons. 16) In this study, the GM of our cases was 17032.2 grams-force (167.03 Newtons), 14594.8 grams-force (143.13 Newtons), and 12852.1 grams-force (126.04 Newtons) for Groups 1, 2, and 3, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…9) This value range is between 51 and 179.9 Newtons in various human cadaver studies. 4,5,15) Bicer et al, in sheep, they found the rupture tension as 171.9 Newtons. 16) In this study, the GM of our cases was 17032.2 grams-force (167.03 Newtons), 14594.8 grams-force (143.13 Newtons), and 12852.1 grams-force (126.04 Newtons) for Groups 1, 2, and 3, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have been performed to assess the tension in the anastomosis line. 49) However, studies investigating the tension required for anastomosis rupture are very limited. Although it is quite rare (4%–14.2%), over-tension on an anastomosis may cause dehiscence.…”
Section: Introductionmentioning
confidence: 99%
“…8 Besides, various methods and materials were also employedsuch as cartilage reinforcement sutures, albumin-glutaraldehyde tissue adhesive, fascia lata, halo vest, braces, and orthoses. [9][10][11][12][13] Fibrin glue is another material used in tracheal anastomosis for sealing, but it has a weak tensile strength. 7 N-butyl-2-cyanoacrylate (NBCA) is an agent that was licensed to be used in skin closure.…”
mentioning
confidence: 99%
“…Chin‐to‐chest suture and releasing maneuvers are known methods to stabilize anastomosis and to decrease tension 8 . Besides, various methods and materials were also employed—such as cartilage reinforcement sutures, albumin‐glutaraldehyde tissue adhesive, fascia lata, halo vest, braces, and orthoses 9‐13 . Fibrin glue is another material used in tracheal anastomosis for sealing, but it has a weak tensile strength 7 …”
mentioning
confidence: 99%
“…There have been studies conducted to evaluate strength and tension at the anastomosis site by means of suture types and techniques. [5][6][7][8][9][10] However, the effect of intraluminal pressure on tracheal anastomoses remains unclear. This issue must be examined, as postoperative coughing is one of the problems after tracheal anastomoses.…”
mentioning
confidence: 99%